Model Pendekatan Misi Perkotaan Melalui Kelompok Penemuan Alkitab - Sugiharto, Ayub; Kurnianto, Putut Agung (Sekolah Tinggi Teologi Berita Hidup, 2025)
Urban missions experienced an important shift from mission models focused on evangelization and individual conversion to more holistic and inclusive strategies. A mission approach is needed that is relevant to the problems and needs of urban communities, so that there are real solutions that can be felt by the community. By understanding the shift from the mission model, the church should be increasingly aware of its being sent by the Lord Jesus Himself to reach souls who do not yet know Him. In the midst of a very large number of communities with increasingly complex life problems and increasing levels of difficulty, today's churches are not only expected to be able to live adaptably in the midst of the community, but the church also needs to see opportunities to take part in soul winning. Using descriptive qualitative methods, researchers explain what is meant by urban mission and what methods are appropriate to use at this time. This research aims to conduct an in-depth analysis of the urban mission model with the social conditions and lifestyle of urban communities. The results show that the group pattern of biblical discovery is very relevant and very likely to be used as a tool of evangelism, given the trend of group lifestyle in social interaction.